Is the concept of personality capacious enough to incorporate virtues? - Fowers, Blaine J.; Novak, Lukas F.; Kiknadze, Nona C.; Selim, Marah (Frontiers in Psychology, 2023)
We will consider four answers to the question about whether the concept of personality is capacious enough to incorporate virtues. The simplest is that the concept of personality encompasses all individual variations in persons. It follows from this answer that virtues would, as individual differences, be incorporated into personality. Unfortunately, definitions of personality do not always invoke such capaciousness, and, in practice, most scholars limit their work to the Big Five or HEXACO models, which do not incorporate virtues. The second answer is that the concept of personality incorporates all trait or dimension level variations across persons, with some exceptions, such as intelligence, attachment style, and psychopathy. Following this definition, virtues, as traits, would be incorporated into such a broad definition of personality. Unfortunately, the boundaries for inclusion and exclusion into personality are fuzzy in this case, and there is no extant definition of personality that solves this problem. The third answer is that personality traits and virtue traits are similar, but distinct concepts. This article presents conceptual and empirical arguments for this similarity in seeing traits as a higher order concept that includes the species of personality and the species of virtue. The fourth answer is that personality and virtue are unrelated. This answer is dismissed because there are many studies that indicate that they are correlated, and few advocate such a clear differentiation. The conclusion is that, pending conceptual and empirical results indicating otherwise, the genus-species relationship seems most fitting where traits are a genus, and personality and virtue are each a species within that genus.